FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN STANDAR PELAYANAN MINIMAL PEMERINTAH KOTA PAYAKUMBUH - Suci Ramadhani; Roni Ekha Putera (Halu Oleo University, 2024)
This study aims to examine the effect of HR competencies and information technology on the quality of the Minimum Service Standards (MSS) report moderated by an organizational commitment among Payakumbuh City Government employees in West Sumatra. A quantitative approach with hypothesis-testing techniques was used in this study. There were 35 samples with the purposive sampling technique, namely officials and employees who were directly involved in the preparation of the SPM Report, namely the Head of SKPD, PPK, and Subag Program. Data was collected by distributing questionnaires in the form of questionnaires and processed using SmartPLS 3.0 software. The data analysis method uses structural equation modelling. The results showed that HR competence had a positive but insignificant effect on the quality of SPM reports, information technology had a positive but insignificant effect on the quality of SPM reports, and organizational commitment had a positive and significant effect on the quality of SPM reports. Organizational commitment was unable to moderate the relationship between HR competence and information technology with the quality of SPM reports. The research implications emphasize the importance of maximizing HR competencies, information technology, and employee commitment when working so as to improve performance.